2019
DOI: 10.1186/s12936-019-3057-7
|View full text |Cite
|
Sign up to set email alerts
|

Markers of sulfadoxine–pyrimethamine resistance in Eastern Democratic Republic of Congo; implications for malaria chemoprevention

Abstract: Background: Sulfadoxine-pyrimethamine (SP) is a cornerstone of malaria chemoprophylaxis and is considered for programmes in the Democratic Republic of Congo (DRC). However, SP efficacy is threatened by drug resistance, that is conferred by mutations in the dhfr and dhps genes. The World Health Organization has specified that intermittent preventive treatment for infants (IPTi) with SP should be implemented only if the prevalence of the dhps K540E mutation is under 50%. There are limited current data on the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…pfdhps genes that confer increased resistance to SP, for example, pfdhps K540E, A581G, and A613S/T mutations, which have been previously correlated with high levels of SP resistance (12). However, the prevalence of these mutations is lower in west and central Africa compared to eastern and southern Africa.…”
mentioning
confidence: 99%
“…pfdhps genes that confer increased resistance to SP, for example, pfdhps K540E, A581G, and A613S/T mutations, which have been previously correlated with high levels of SP resistance (12). However, the prevalence of these mutations is lower in west and central Africa compared to eastern and southern Africa.…”
mentioning
confidence: 99%
“…Resistance to SP or AQ may reduce the efficacy of SMC in protecting children against clinical malaria, although the relationship between the degree of resistance and the effectiveness of SMC has not yet been clearly defined. SP efficacy is threatened by drug resistance due to mutations in the dihydrofolate reductase ( dhfr ) and dihydropteroate synthetase ( dhps ) genes [ 17 ]. According to a study conducted in Mozambique, the prevalence of dhfr and dhps mutations was 5%-6% [ 18 ], with more recent research suggesting this may be as high as >80% [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Investigation of the adherence to the 3x AQ regimen within one treatment course in a clinical trial in Niger showed that only 20% of children received the full regimen 10 . Additionally, the spread of resistance markers against SP was reported with increasing SMC deployment 11,12 , impacting the eligibility of regions for SMC 13 as well as the protective efficacy after implementation 14 .…”
Section: Introductionmentioning
confidence: 99%